26.2k views
0 votes
Multiply and simplify: (6x + 3y)(6x − 3y)

User Ayu
by
6.1k points

2 Answers

2 votes

Answer:

36x² - 9y²

Explanation:

(6x + 3y)(6x − 3y)

(6x)² - (3y)²

36x² - 9y²

User Apnorton
by
6.3k points
1 vote

Answer:

36x² - 9y²

Explanation:

We see that the given expression (6x + 3y)(6x - 3y) looks just like the expression (a + b)(a - b). When multiplied out, this is a difference of squares identity that I highly recommend you memorise:

(a + b)(a - b) = a² - b²

Here, a = 6x and b = 3y, so plug these in:

(6x + 3y)(6x - 3y) = (6x)² - (3y)² = 36x² - 9y²